HUBUNGAN PERILAKU MAKAN, ASUPAN ENERGI, ASUPAN ZAT GIZI MAKRO, DAN PENERAPAN DIET GLUTEN FREE CASEIN FREE DENGAN STATUS GIZI ANAK AUTISM SPECTRUM DISORDER (ASD) DI WILAYAH JABODETABEK TAHUN 2023 - Nabila Aprilia, (2023)
The increasing prevalance of people with autism in various countries cannot be separated from the emergence of problems, especially nutritional ones. Nutritional problems that occur in people with autism are the same as those that occur in normal children in general. These nutritional problems are caused by several factors, including eating behavior disorders, strict diet therapy, and unbalanced food intake, which can increase the risk of undernutrition or even overnutrition. The purpose of this study was to determine the relationship between eating behavior, energy intake, macronutrient intake, and the application of the Gluten-Free Casein-Free (GFCF) diet with the nutritional status of Autism children in Jabodetabek. This study used a cross-sectional study design with quota sampling techniques. The sample in this study was 101 children with ASD. Data analysis in this study used the spearman rank test. The results of the bivariate showed no relationship between eating behavior (p = 0.300, r=0,098), protein intake (p = 0.223, r= 0,115), fat intake (p=0,083, r=0,163) and the Implementation of the GFCF diet (p = 0.544, r=-0,544) with nutritional status. but there is a relationship between energy intake (0 = 0.002, r=0,293), and carbohydrate intake (p = 0.00, r=0,382) with the nutritional status of ASD children in Jabodetabek. There is a need to analyze other factors that can affect the nutritional status of ASD children.